Plant terpenes that mediate below‐ground interactions: prospects for bioengineering terpenoids for plant protection - Huang, Ancheng C (Pest Manag Sci, 2019)
Plants are sessile organisms that have evolved various mechanisms to adapt to complex and changing environments. One important feature of plant adaption is the production of specialised metabolites. Terpenes are the largest class of specialised metabolites, with over 80 000 structures reported so far, and they have important ecological functions in plant adaptation. Here, we review the current knowledge on plant terpenes that mediate below‐ground interactions between plants and other organisms, including microbes, herbivores and other plants. The discovery, functions and biosynthesis of these terpenes are discussed, and prospects for bioengineering terpenoids for plant protection are considered. © 2019 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.